58.2k views
0 votes
Simplify (x − 3)(x2+ 7x − 8).

User Msalman
by
6.2k points

1 Answer

3 votes

Greetings!

Answer:

x³ + 4x² -29x + 24

Explanation:

Firstly, lets multiply everything in the second bracket by x:

x(x² + 7x - 8)

x * x² = x³

x * 7x = 7x²

-8 * x = -8x

= x³ + 7x² - 8x

Now multiply everything by -3:

-3(x² + 7x -8)

-3 * x² = -3x²

-3 * 7x = -21x

-3 * -8 = 24

-3x² -21x + 24

Put the two equations in one:

x³ + 7x² - 8x -3x² -21x + 24

x³ stays the same as it is the only one,

7x² - 3x² = 4x²

-8x + -21x = -8x - 21x = -29x

24 stays the same.

Simply put the values above together:

x³ + 4x² -29x + 24


Hope this helps!


User Minoo
by
5.1k points